2013
DOI: 10.1152/ajpcell.00139.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cyp1B1 expression promotes angiogenesis by suppressing NF-κB activity

Abstract: Nuclear factor-κB (NF-κB) is a master regulator of genes that control a large number of cellular processes, including angiogenesis and inflammation. We recently demonstrated that cytochrome P-450 1B1 (Cyp1B1) deficiency in endothelial cells (EC) and pericytes (PC) results in increased oxidative stress, alterations in migration, attenuation of capillary morphogenesis, sustained activation of NF-κB, and increased expression of thrombospondin-2 (TSP2), an endogenous inhibitor of angiogenesis. On the basis of a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 48 publications
2
64
0
Order By: Relevance
“…We have observed TSP2-GFP expression in retinal vasculature, and predominantly in perivascular supporting cells. 17 The intensity of the green fluorescence increased during the postnatal development of the retinal vascculature in older animals, but it was almost undetectable at later postnatal time (P42). These results were further confirmed by the western blot analysis of GFP protein.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We have observed TSP2-GFP expression in retinal vasculature, and predominantly in perivascular supporting cells. 17 The intensity of the green fluorescence increased during the postnatal development of the retinal vascculature in older animals, but it was almost undetectable at later postnatal time (P42). These results were further confirmed by the western blot analysis of GFP protein.…”
Section: Discussionmentioning
confidence: 96%
“…The generation of a line of TSP2 reporter transgenic mice, where endogenous TSP2 promoter drives expression of green fluorescent protein (GFP), was previously described. 17 The following primers were used for screening of the transgene: GFP forward: 5¢-CCTACGGC GTGCAGT GCTTCAGC-3¢; and GFP reverse: 5¢-CGGCG AGCTGCACGCTGCGTCCTC-3¢.…”
Section: Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The major phenotypic features associated with CYP1B1 deletion include protection from the deleterious effects of excess dietary fat, including oxidative stress, hepatic steatosis, and T2D [32]. Recently microarray data from the livers of the CYP1B1 KO mice that are resistant to diet-induced obesity indicated that CYP1B1 deletion substantially alters the expression of genes associated with fatty acid homeostasis [33].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was linked with a decrease in the expression of eNOS , as well as a corresponding increase in intracellular oxidative stress and increased production of thrombospondin-2, an endogenous inhibitor of angiogenesis (Tang et al, 2009;Palenski et al, 2013). Interestingly, estrogen-induced angiogenesis has also been attributed to changes in eNOS, thrombospondin, and free radical generation, making it tempting to speculate that CYP1B1 may actually mediate the effects of the hormone.…”
Section: Inflammation and Resolution Of Inflammationmentioning
confidence: 99%